Postoperative adjuvant antiviral therapy for hepatitis B/C virus-related hepatocellular carcinoma: A meta-analysis - Miao, Ruo-Yu (Baishideng, 2010)
AIM: To investigate the impact of postoperative antiviral treatment on tumor recurrence and survival of patients with chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infection-related primary hepatocellular carcinoma (HCC) after curative therapy. METHODS: We performed a meta-analysis of randomized and non-randomized control trials from electronic search and manual search. The fixed effect model of Mantel-Haenszel method and the random effect model of Der Simonian and Laird method were used for homogeneous and heterogeneous studies, respectively. Seven HCV-related studies, three HBV-related studies and three studies on HBV or HCV-related HCC were identified. RESULTS: A total of 1224 patients were included in this analysis. The estimated odds ratios (OR) for the 1-, 2-, 3- and 5-year recurrence were 0.54 [15.4% vs 24.1%, 95% confidence interval (CI): 0.32-0.89, P = 0.02], 0.42 (36.9% vs 58.0%, 95% CI: 0.19-0.90, P = 0.03), 0.37 (47.9% vs 63.8%, 95% CI: 0.19-0.71, P = 0.003), and 0.32 (66.7% vs 74.3%, 95% CI: 0.15-0.66, P = 0.002), respectively; and the OR for the 1-, 2-, 3-, 5- and 7-year mortality were 0.23 (1.2% vs 9.1%, 95% CI: 0.07-0.71, P = 0.01), 0.31 (6.4% vs 22.1%, 95% CI: 0.12-0.79, P = 0.01), 0.43 (12.7% vs 20.8%, 95% CI: 0.21-0.89, P = 0.02), 0.42 (25.1% vs 42.0%, 95% CI: 0.27-0.66, P = 0.0002) and 0.28 (31.9% vs 52.2%, 95% CI: 0.13-0.59, P = 0.0008). CONCLUSION: This meta-analysis indicates the postoperative antiviral therapy, interferon in particular, may serve as a favorable alternative to reduce recurrence and mortality in patients with HBV/HCV related HCCs.